3rd ICTs and Society Meeting; Paper Session - Inequalities: social, economic, political; Paper 1: Information Society Policies 2.0. A Critical Analysis of the Potential and Pitfalls of Social Computing & Informatics in the Light of Einclusion. (2010) - Verdegem, Pieter
No abstract available